Sense of coherence as influencing information sharing at the workplace - Heinström Jannica; Ahmad Farhan; Huvila Isto; Ek Stefan (Emerald, 2025)
Purpose
This study introduces sense of coherence (SOC) as a factor in information sharing at the workplace.
Design/methodology/approach
Data were collected by a survey conducted on 311 respondents in a multinational organization, and analyzed using partial least square structural equation modelling.
Findings
SOC influenced information sharing both directly and indirectly as mediated by trust and employee learning orientation. Trust, moreover, influenced receiving information more strongly than sending it, while employee learning orientation more strongly affected sending information.
Originality/value
The findings underline the importance of a holistic understanding of information sharing, including individual differences and employee well-being.